Thyroid Fine Needle Aspiration Biopsies in Children: Study of Cytological-Histological Correlation and Immunostaining with Thyroid Peroxidase Monoclonal Antibodies. (31st May 2010) - Hoperia, Victoria; Larin, Alexander; Jensen, Kirk; Bauer, Andrew; Vasko, Vasily
Abstract : Context . There is limited data comparing results of fine needle aspiration biopsies (FNABs) to histological diagnosis in children. Design . FNABs were performed in 707 children and cytological results were compared to histology in 165 cases. The usefulness of immunostaining with anti-TPO monoclonal antibodies (MoAb47) on FNAB samples was examined in 54 operated patients. Results . Among unsatisfactory, benign, suspicious, and malignant FNAB, the histological diagnoses were benign in 12/12 (100%), 69/70 (98.5%), 40/50 (80.0%), and 0/33 (0%), respectively. After surgery, malignancy was established in 44/165 (26.6%) cases. The sensitivity, specificity, and positive and negative predictive values were 95.4%, 55.8%, 61.7%, and 95% with standard FNAB; and 100%, 75%, 73.3, and 100% with MoAb47. Among suspicious FNAB, positive MoAb47 staining was a reliable marker for exclusion of malignancy. Conclusion . Benign and malignant FNAB accurately predict histological diagnosis. In suspicious FNAB, MoAb47 immunostaining may be a useful adjunct to standard cytology.